Optimizing bone health and minimizing skeletal morbidity in men with prostate cancer - McKay, Rana R. (2013)
Maintaining bone health is important in all stages of the management of men with prostate cancer. Patients receiving androgen-deprivation therapy (ADT) are at increased risk of treatment-related osteoporosis and patients with bone metastases are at increased risk of skeletal morbidity related to debilitating skeletal-related events (SREs). Osteoclast-targeted agents have a beneficial impact on bone health in patients with prostate cancer. For patients on ADT at high-risk for fracture, bisphosphonates have been shown to increase bone mineral density (BMD), a surrogate for fracture risk, whereas denosumab (Prolia) has been shown to decrease the risk of osteoporotic fractures, in addition to increasing BMD. For patients with castration-resistant prostate cancer (CRPC) with bone metastases, both zoledronic acid (Zometa) and denosumab (Xgeva) have shown benefit in decreasing the rate of SREs. Currently, no agent is approved for the prevention of bone metastases in high-risk patients. Novel systemic agents including radium-223 (Alpharadin), abiraterone (Zytiga), and enzalutamide (Xtandi) have shown a beneficial effect on the rate of SREs in patients with CRPC with bone metastases by directly impacting tumor growth. Integration of these anti-cancer agents with currently approved osteoclast-targeted agents warrants further investigation.